Comparative genomic analysis uncovered phylogenetic diversity, evolution of virulence factors, and horizontal gene transfer events in tomato bacterial spot Xanthomonas euvesicatoria - Huang, Chien-Jui; Wu, Ting-Li; Wu, Yu-Lin; Wang, Ruei-Shiuan; Lin, Yao-Cheng (Frontiers in Microbiology, 2024)
Introduction Bacterial spot, caused by diverse xanthomonads classified into four lineages within three species, poses a significant threat to global pepper and tomato production. In Taiwan, tomato bacterial spot xanthomonads phylogenetically related to an atypical Xanthomonas euvesicatoria pv. perforans (Xep) strain NI1 from Nigeria were found. Methods To investigate the genetic structure of Taiwanese Xep strains and determine the phylogenetic position of the atypical strains, we completed high-quality, gap-free, circularized genomes of seven Taiwanese Xep strains and performed comparative genomic analyses with genomes of X. euvesicatoria pathovars. Average nucleotide identity, core genome analysis, and phylogenomic analysis were conducted. Results Three sequenced strains were identified as typical Xep, while four clustered with the atypical strain NI1, forming a distinct genomovar within X. euvesicatoria, proposed as X. euvesicatoria genomovar taiwanensis (Xet). This new lineage likely originated in Taiwan and spread to Nigeria through global seed trade. At the genomovar level, chromosomes remained conserved among Taiwanese strains, while plasmids likely contributed to bacterial virulence, avirulence, and field fitness. Gap-free genomes revealed associations between the evolution of type III effectors, horizontal gene transfer events, plasmid diversity, and recombination. Discussion This study highlights the critical roles of horizontal gene transfer and plasmids in shaping the genetic makeup, evolution, and environmental adaptation of plant pathogenic xanthomonads. The identification of a new genomovar, X. euvesicatoria genomovar taiwanensis, provides insights into the diversity and global spread of bacterial spot pathogens through seed trade.